Efficacy of Dexamethasone as an Adjuvant to Caudal Bupivacaine for Infra-umbilical Surgeries in Children: A Prospective Randomised Study - Raghavendra Prasad Saya , Sonu Sesham , Sarah Shahnaz Saifudeen Kitchlu , Suryanarayan Chakali , Sunil Chiruvella (RUHS Journal of Health Sciences, 2024)
Introduction: Caudal block is a popular technique in practice for post-operative pain management in children undergoing infra-umbilical surgeries. However, the duration of analgesia achieved by caudal block is limited by the duration of action of the local anaesthetic. The present study was aimed to evaluate the analgesic effect of Dexamethasone as an adjuvant to caudal Bupivacaine in children undergoing infra-umbilical surgeries. Methodology: The present study was conducted on children aged between 2-6 years who were scheduled for elective infra-umbilical surgery. All children received general anaesthesia. Children in group A received caudal block with 1 ml/kg of 0.125% Bupivacaine and 1 ml normal saline and children in group B received caudal block with 1 ml/kg of 0.125% Bupivacaine and 0.1 mg/kg Dexamethasone. Collected data were analyzed using Medcalc software. Quantitative data was analyzed using student's t test and categorical data analyzed using the chi square test. Results: The mean duration of analgesia was significantly prolonged in group B as compared to group A (657±95.6 minute and 221.2±51.2 minute respectively) (p< 0.0001). Post-operative pain score was significantly less in group B at 2, 3, 4, 8, 12, 20, and 24 hours, respectively (p <0.0001). Requirement of rescue analgesia was significantly less in group B (p<0.0001). None of the patients had wound infection or vomiting. Conclusion: Dexamethasone is safe and effective to use as an adjuvant to caudal Bupivacaine for prolongation of duration of analgesia in children undergoing infra-umbilical surgeries.